A Study on Job Satisfaction of Special Education Teachers in Zhuhai, China - Xiong, Xue (Environment and Social Psychology, 2025)
As a cornerstone of China’s education system, special education relies primarily on special education teachers as its core implementers. While existing literature has begun to focus on and investigate the job satisfaction of special education teachers and its influencing factors, such studies have mostly been confined to analyzing material-oriented satisfaction dimensions—most notably the salary levels of full-time special education teachers. Consequently, research into the professional development and psychological fulfillment of full-time special education teachers holds greater academic and practical significance. Guided by the diversified education theory, this study developed a questionnaire to collect data from full-time special education teachers at special education schools in Zhuhai. After conducting questionnaire screening and data cleaning, the study analyzes both the overall job satisfaction level of full-time special education teachers in the region and the specific factors influencing their job satisfaction. Furthermore, based on the questionnaire findings, this study puts forward targeted recommendations to enhance the job satisfaction of special education teachers in Zhuhai, thereby contributing to the high-quality development of education in the city.